Combinatorial gene regulatory functions underlie ultraconserved elements in drosophila - Warnefors, Maria; Hartmann, Britta; Thomsen, Stefan; Alonso, Claudio R. (Molecular biology and evolution, 2016)
Abstract. Ultraconserved elements (UCEs) are discrete genomic elements conserved across large evolutionary distances. Although UCEs have been linked to multipl
Advance access publication May 31, 2016
Gesehen am 10.06.2020